Characteristics of in situ stress field of coalbed methane reservoir and its influence on permeability in western Guizhou coalfield, China - Lv, Fang; Yang, Ruidong; Yi, Tongsheng; Gao, Wei; Wang, Xu; Cheng, Wei; Zhang, Yan; Li, Ronglei; Yan, Zhihua; Liu, Yaohui; Li, Geng (Frontiers in Earth Science, 2023)
In-situ stress is an important indicator for the preferential selection of coalbed methane (CBM) exploration dessert zones, and is a key factor affecting the production capacity of coalbed methane wells. Coal reservoir permeability is one of the key parameters to evaluate the recoverability and modifiability of coalbed methane and reflects the seepage capacity of coal reservoirs. In this study, in situ stress data were collected from multiple injection/fall-off tests of multiple parameter wells in western Guizhou province, China The relationships among parameters such as pore pressure (Pp), closure pressure (Pc), breakdown pressure (Pb), in situ stress, coal permeability, and depth were explore. Using Anderson’s classification method, the distribution of three different in situ stress states was counted. A new simplified model diagram of triaxial principal stress and depth in the study area is proposed by linearly fitting the triaxial principal stress and burial depth. The envelope equation and median equation of the lateral pressure coefficient k-value stress ratio with depth of burial obtained by Brown and Hoek method were calculated using hyperbolic regression algorithm. The k-values were found to be discrete at shallower depths and converge at deeper depths, gradually converging to .65. The control of in situ stress on the permeability of coal reservoirs was explored, and a strong positive correlation was found between the permeability and the Z-shaped variation of the lateral pressure coefficient k-values at shallow depths of 1,000 m. Also, the distribution pattern of vertical permeability basically corresponds to the stress transition zone from the strike-slip fault mode to the normal fault mode. The coal seam permeability has a strong sensitivity to effective in situ stress (EIS). In this study, the least squares method with multiple fitting of power exponents is applied to analyze the control mechanism of EIS on permeability in depth and reveal a new relationship between permeability and EIS that is different from that considered by previous authors. Summarizing the above research results, the vertical CBM in western Guizhou is divided into three development potential zones, and 400–1,000 m burial depth is the most favorable vertical development zone.